Development of "flexible" compositional skills in training future art specialists (Pedagogy of Higher and Secondary Education, 2009)
Article is devoted a problem of formation of "flexible" composite abilities as certain action in composite creative activity of students.
Keywords: flexibility; plasticity; composite abilities; skills; system of composite exercises